2008
DOI: 10.1515/bc.2009.015
|View full text |Cite
|
Sign up to set email alerts
|

Functional genetic mouse models: promising tools for investigation of the proteolytic internet

Abstract: Knockout mice are the gold standard to probe for the role of a specific protease within the interacting network of proteases, substrates, and inhibitors. This proteolytic network, or protease web, determines cell signaling and organ homeostasis. Therefore, protease deficiency or inhibition is intrinsically tied to alterations within this network, always leading to new molecular phenotypes, which define susceptibility of an organ to disease. Furthermore, recent hints, mainly from research on matrix metalloprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Inhibition of MMP-9 is currently tested as therapeutic approach in clinical trials (11), despite the seminal failure of MMP inhibitors in the past (5), because increased selectivity of inhibitors for target MMPs is thought to be key to the expected antitumorigenic and antimetastatic therapeutic potential of MMP inhibition (8,9). However, functions of specific MMPs can be context dependent (28). Thus, critical assessment of potential target MMPs in relevant disease contexts is imperative to their evaluation as therapeutic targets (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of MMP-9 is currently tested as therapeutic approach in clinical trials (11), despite the seminal failure of MMP inhibitors in the past (5), because increased selectivity of inhibitors for target MMPs is thought to be key to the expected antitumorigenic and antimetastatic therapeutic potential of MMP inhibition (8,9). However, functions of specific MMPs can be context dependent (28). Thus, critical assessment of potential target MMPs in relevant disease contexts is imperative to their evaluation as therapeutic targets (12).…”
Section: Discussionmentioning
confidence: 99%
“…We thus hypothesized that systemic alterations in the MMP-9-deficient hosts promoted the invasive growth of PDAC. Previously, we have shown that MMP-9 knockout can result in specific induction of IL6 in the bone marrow (28). Noteworthy, elevated systemic and tumoral IL6 levels derived from the bone marrow were recently shown to be central to PDAC initiation and progression (29) by acting on various tumorpromoting processes including tumor cell proliferation, survival, migration, invasion (i.e., invasive growth) as well as angiogenesis, activation of stromal fibroblasts, and immune invasion (30).…”
Section: G12d -Lsl-trp53mentioning
confidence: 99%
“…However the utility of MMP knockout models is questionable due to compensatory upregulation of other MMPs [47,48] , and because of conflicting results in cancer studies [49] , where MMPs were highly involved in cancer progression.…”
Section: Targeting Mmp-9mentioning
confidence: 99%
“…Moreover, the use of MMP-KO model has yielded conflicting results in various disease models. 20 Recent studies from our group have demonstrated that MMP-9 itself is capable of inducing the entire course of tubular cell EMT via the disruption of E-cadherin/b-cateninmediated cell-to-cell adhesion complex, independent of epithelial cell-basement membrane disruption. 6,21 Moreover, results from our in vitro study has highlighted a prominent role and potentially an important source of MMP-9 from macrophages and TEC in tubular cell EMT induction, which has not previously been addressed in renal fibrosis.…”
mentioning
confidence: 99%